La Perception De L’image De Marque Automobile: Étude Qualitative Exploratoire Auprès Des Consommateurs De La Ville d’Agadir - Hamri, Mohammed Hicham; Qanqom, Amira (European Scientific Journal, ESJ, 2018)
This paper focuses on conducting an exploratory study that allows us to discover how people in Agadir city can construct an image of an automobile brand. Indeed, in the automotive sector, brands are very important and the image is one of the priorities to last on the market. As a result, a lot of companies have attached a significant importance to the measurement of their brand image to consumers. In this study, we are going to base our work on the main typologies of brand image, namely Korchia (2001), which allows its measurement. Also, we will take a case study of them in regards to our field of study. At the end of this paper, we aim to design our own typology. For that purpose, we conducted a qualitative study, by individual interviews. As a conclusion, this work is dedicated to develop a brand image typology, specific to automotive sector, and adapted to Agadir city consumers.